Are breeding sites a limiting factor for the Tandilean redbelly toad (Bufonidae) in pampean highland grasslands? - Cortelezzi, Agustina (2015)
The selection of breeding sites in response to temporary pond characteristics has been frequently documented in several anuran species. Small and shallow temporary ponds are usually preferred. The Tandilean red-belly toad, Melanophryniscus aff. montevidensis, is an endemic species that breeds in temporary ponds of remnants of highland grasslands in Tandilia mountain system, Buenos Aires Province, Argentina. The goals of this work are to characterize breeding sites of Tandilean red-belly toad, and to assess the availability of potential breeding sites at remnants of highland grasslands. Tandilean red-belly toad was observed using ponds and temporary creeks in valleys and slopes of mountains. The median of dimensions for the breeding sites was 8m length, 4m wide and 10cm depth (n = 40). The majority of the breeding sites were circular and of natural origin. The dominant breeding site substrates were mud and vegetation. We found 115 potential breeding sites in grassland remnants of surroundings of Tandil city, giving a density of 7.1 potential breeding sites/km2. The density of potential breeding sites in highland grasslands of Tandilia Mountains was similar in most surveyed remnants. Therefore, our results suggest that size of remnant is not affecting the breeding habitat availability.